Common variants in the CLDN2-MORC4 and PRSS1-PRSS2 loci confer susceptibility to acute pancreatitis - Weiss, Frank Ulrich; Hesselbarth, Nico; Párniczky, Andrea; Mosztbacher, Dora; Lämmerhirt, Felix; Ruffert, Claudia; Kovacs, Peter; Beer, Sebastian; Seltsam, Katharina; Griesmann, Heidi; Böhme, Richard; Kaune, Tom; et al. (Pancreatology (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.]), 2018)
BACKGROUND/OBJECTIVES Acute pancreatitis (AP) is one of the most common gastrointestinal disorders often requiring hospitalization. Frequent aetiologies are gallstones and alcohol abuse. In contrast to chronic pancreatitis (CP) few robust genetic associations have been described. Here we analysed whether common variants in the CLDN2-MORC4 and the PRSS1-PRSS2 locus that increase recurrent AP and CP risk associate with AP. METHODS We screened 1462 AP patients and 3999 controls with melting curve analysis for SNPs rs10273639 (PRSS1-PRSS2), rs7057398 (RIPPLY), and rs12688220 (MORC4). Calculations were performed for the overall group, aetiology, and gender sub-groups. To examine genotype-phenotype relationships we performed several meta-analyses. RESULTS Meta-analyses of all AP patients depicted significant (p-value < 0.05) associations for rs10273639 (odds ratio (OR) 0.88, 95% confidence interval (CI) 0.81-0.97, p-value 0.01), rs7057398 (OR 1.27, 95% CI 1.07-1.5, p-value 0.005), and rs12688220 (OR 1.32, 95% CI 1.12-1.56, p-value 0.001). For the different aetiology groups a significant association was shown for rs10273639 (OR 0.76, 95% CI 0.63-0.92, p-value 0.005), rs7057398 (OR 1.43, 95% CI 1.07-1.92, p-value 0.02), and rs12688220 (OR 1.44, 95% CI 1.07-1.93, p-value 0.02) in the alcoholic sub-group only. CONCLUSIONS The association of CP risk variants with different AP aetiologies, which is strongest in the alcoholic AP group, might implicate common pathomechanisms most likely between alcoholic AP and CP.